Development of speed-strength abilities of 11-12 year old rugby players using a set of special exercises - Vladlena Pasko; Olena Nesen; Anatolii Tsos; Irina Pomeshchikova; Ludmila Filenko; Olena Tserkovna; Natalia Dolgopolova (Kharkiv State Academy of Physical Culture, 2023)
Purpose: to select and experimentally test the effectiveness of complexes of special exercises for the development of speed-strength abilities of rugby players at the stage of preliminary basic training. Material of the study: the study involved 24 young athletes aged 11-12 years who trained at the stage of preliminary basic training. Research methods: indicators of speed-strength abilities of 11-12 year old rugby players were determined using the following tests: 30 m run from a high start, standing long jump, triple jump, 30 m run with a ball, shuttle run (3x10 m), passing the ball in pairs. Results: a different degree of correlation was established between the indicators of test exercises that were used to determine the speed-strength abilities of 11-12-year-old rugby players: between the results of tests of running 30 meters from a high start, standing long jump, a triple jump from a place and running to 30 meters with the ball, and between the 30 meters run with the ball and the shuttle run 3 x 10 meters - a significant relationship (r=0,712-0,817). Between the results of standing long jump, a shuttle run of 3 to 10 meters and the number of ball passes on the spot in pairs, there is a low degree of manifestation (r = 0,309-0,455). Between the indicators of other test exercises that were used in our study, a moderately pronounced relationship was established (r=0,499-0,674). Conclusions: the effectiveness of the use of complexes of special exercises for the development of speed-strength abilities of rugby players at the stage of preliminary basic training has been proven. Significant differences between the test results of the control and experimental groups were established: 30 m run, standing long jump, triple jump, 30 m run with the ball, passing the ball in pairs.